EVALUATING DIGITAL LEARNING APPLICATION IN UNIVERSITY SETTING: INDONESIAN STUDENTS’ EXPERIENCES, CHALLENGES, AND LEARNING EFFECTIVENESS - SITI CHOIRIYAH (Perkumpulan Cendekia Muda Kreatif Indonesia, 2023)
The closure of educational institutions due to the recent COVID-19 pandemic has resulted in a significant shift from traditional face-to-face learning to online activities. This unexpected change has brought about various challenges, issues, potentials, and other factors pertaining to the implementation of online teaching and learning. This research aims to elucidate the learning experiences of college students in Indonesia. A narrative inquiry approach employing written reflections and semi-structured interviews is utilized to investigate the online learning encounters of 23 university students studying at an Islamic education department at UIN Raden Mas Said Surakarta Indonesia. The findings of this study reveal that social media platforms have predominantly shaped the landscape of higher education learning experiences for the participating students. Despite admitting to being ill-prepared and facing challenges such as power supply disruptions, unstable internet connections, and limited access to digital devices, the students exhibited a notable enthusiasm for engaging in online learning activities. When sharing their opinions on instructional methods, a majority of them expressed a preference for the traditional face-to-face classroom interaction. These findings underscore the practical need for teachers and relevant stakeholders to enhance the effectiveness of online learning endeavors in Indonesia.